Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) pada Pembelajaran Fisika Siswa - Eva Juwita; Wahyu Ariani; Endang Lovisia; Sulistiyono Sulistiyono; Yaspin Yolanda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Abstract: This study aims to measure the science learning outcomes of grade VIII.1 students at Sukamana State Junior High School after implementing the Contextual Teaching and Learning (CTL) model. This research method was conducted in three meetings consisting of a pre-test, learning with the CTL model, and a post-test. The results of the pre-test of 33 students showed an average score of 58.8 with a standard deviation of 11.9, with only 3 students achieving a score of 70 or higher. After learning using the CTL model, post-test scores showed a significant increase, with an average of 89, the highest score being 100, and the lowest score being 60. This increase indicates that students have successfully understood the material on vibrations, waves, and sound and are able to relate it to examples in everyday life. Based on the comparison of the pre-test and post-test results, it can be concluded that the implementation of the CTL learning model successfully improved student learning outcomes. Keywords: Learning Outcomes, Pretest, Posttest, CTL